IMPROVING STUDENTS’ NARRATIVE WRITING BY USING WH-QUESTIONS AS A GUIDE - Puspitasari, Hesty; Supardi, Iwan; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research purpose is to see how far the improvement of students’ narrative writing has been made by using WH-Questions as a guide. The research method that used is a classroom action research and the data were collected by direct observation technique in the teaching learning process through field notes as the tools of research. The research was conducted in two cycles. The first cycle was conducted on 28 October 2011 and the second cycle on 3 November 2011. After conducting the research, the writer got the data which show that WH-Questions increased the students’ narrative writing in the classroom activity. The finding of this research showed that WH-Questions can help students to improve students’narrative writing, it is looked by the score from 58.13 at first cycle and 78.39 at second cycle.Keywords: WH-Questions, narrative writing